Kathy Acker Writing the Impossible - Colby, Georgina (Edinburgh University Press, 2022)
An in-depth analysis of the work of one of the twentieth century's most innovative writersKathy Acker's body of work is one of the most significant collections of experimental writing in English. In Kathy Acker: Writing the Impossible, Georgina Colby explores Acker's compositional processes and intricate experimental practices, from early poetic exercises written in the 1970s to her final writings in 1997. Through original archival research, Colby traces the stages in Acker's writing and draws on her knowledge of unpublished manuscripts, notebooks, essays, illustrations, and correspondence to produce new ways of reading Acker's works. Rather than treating Acker as a postmodern writer this book argues that Acker continued a radical modernist engagement with the crisis of language, and carried out a series of experiments in composition and writing that are comparable in scope and rigor to her modernist predecessors Stein and Joyce. Each chapter focuses on a particular compositional method and insists on the importance of avant-garde experiment to the process of making new non-conventional modes of meaning. Combining close attention to the form of Acker's experimental writings with a consideration of the literary cultures from which she emerged, Colby positions Acker as a key figure in the American avant-garde, and a pioneer of contemporary experimental women's writing.Key FeaturesExamines unpublished manuscripts, notebooks, lecture notes, letters and manuscripts from the Kathy Acker PapersFeatures eleven previously unpublished images of original manuscripts, correspondence, and colour illustrations from the Kathy Acker PapersUtilises major archival study of Acker's experimental compositional practicesSituates Acker as a late modernist writer and a key figure in the American Avant-Garde
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Mrz 2022)
Keywords: Literary Studies; LITERARY CRITICISM / Feminist